2016
DOI: 10.1039/c5cp07357j
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional transition-metal oxide monolayers as cathode materials for Li and Na ion batteries

Abstract: Two-dimensional monolayers are attractive for applications in metal-ion batteries because of their low ion-diffusion barrier and volume expansion. In this work, we carry out a first-principles study on electrochemical and structural properties of two-dimensional (2D) oxide monolayers and investigate their applications in metal-ion batteries. 2D transition-metal oxide monolayers (MO2; M = Mn, Co, and Ni) with various ion-intercalation densities are systematically studied. Our calculations show that Li and Na at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 45 publications
(52 reference statements)
2
40
0
Order By: Relevance
“…Many 2D materials as anode for LIBs/NIBs have been widely demonstrated in both experiment and theory. For instance, graphene derived from splitting graphite oxide has been widely explored as anode materials . It has been predicted that borophene had a high theoretical capacity (1860 mAh/g), low diffusion barrier and low average open circuit voltage, suggesting its great potential used as anode for LIBs .…”
Section: Introductionsupporting
confidence: 77%
“…Many 2D materials as anode for LIBs/NIBs have been widely demonstrated in both experiment and theory. For instance, graphene derived from splitting graphite oxide has been widely explored as anode materials . It has been predicted that borophene had a high theoretical capacity (1860 mAh/g), low diffusion barrier and low average open circuit voltage, suggesting its great potential used as anode for LIBs .…”
Section: Introductionsupporting
confidence: 77%
“…The favorable ion‐transport properties of 2D metal oxides relative to bulk materials are a driving force behind their exploration . For example, the diffusion barrier for Li in MnO 2 is 0.26 eV in bulk but 0.15 eV in monolayers.…”
Section: Energy Storagementioning
confidence: 99%
“…Owing to its unique physicochemical properties, and environmental and biological compatibility, MnO 2 has attracted wide research interest and found diverse potential applications including cell batteries [23,24], catalyst [25][26][27][28], sensing [29,30], and biological uses in the magnetic resonance imaging and drug delivery [31,32].…”
Section: Introductionmentioning
confidence: 99%